Із Василем Блакитним проти Валер’яна Поліщука: фрагменти суспільно-літературної діяльності Євгена Касяненка - Омельчук, О. (Слово і Час, 2022)
У статті подано невідомі сторінки творчої біографії Євгена Івановича
Касяненка (1889—1937) — одного з піонерів українського авіабудування, перекладача, активного учасника громадсько-політичного і літературного руху 1910—1930-х років. Основою дослідження є реконструкція
літературно-виробничих відносин між Є. Касяненком, Василем Елланом-Блакитним та Валер’яном Поліщуком, висвітлення їхніх поглядів щодо
організаційних і концептуальних форм українського письменства. Аналіз
ініційованих ними проєктів і полемік актуалізує питання про культурно-історичні витоки «Червоного ренесансу» та специфіку формування української літератури як пролетарської. The paper covers unknown pages of Yevhen Kasianenko’s creative activity. Yevhen Kasianenko
(1889—1937) was one of the pioneers of Ukrainian aircraft construction, a translator,
and an active participant in the socio-political and literary movement of the 1910s—1930s.
The study reconstructs the literary and business relations between Yevhen Kasianenko, Vasyl
Ellan-Blakytnyi, and Valerian Polishchuk. The author analyzes their views on organizational
and conceptual forms of Ukrainian literature. The analysis of the projects and polemics initiated
by the writers tackles the question of the cultural and historical origins of the ‘Red
Renaissance’ and the specifical formation of the Ukrainian proletarian literature.
This paper explores Yevhen Kasianenko’s involvement in the press of the Ukrainian
People’s Republic period, his participation in the emergence of Ukrainian-language Soviet
periodicals, the first associations of proletarian writers, and Ukrainian publishing houses, as
well as his role in communication between Soviet writers and émigré artists. The study analyzes
for the first time the criminal case against Kasianenko and outlines his extensive connections
within the Ukrainian literary environment. Kasianenko was one of those whose
activity the Russian Communist Party leadership used for Sovietization policies in Ukraine
as well as for the Ukrainization of the Bolshevik policy. He contributed to legitimizing the
party’s political practices and symbolic images. Kasianenko’s biography shows that in ideological,
scholarly, and cultural aspects, the Soviet civilization project was not radically innovative,
largely existing in the orbit of the pre-revolutionary socio-cultural movement.